Smartphone Addiction and Psychological Well-being Among College Students: The Moderating Role of Gender and Smartphone Usage Duration - Pratiwi, Ratri; Rinaldi, Martaria Rizky; Putra Kurniawan, Aditya (Gadjah Mada Journal of Psychology (GamaJoP), 2025)
Proactive personality is an essential disposition determining students’ readiness to enter the workforce, so a validated instrument is needed to measure it in Indonesia. This study aimed to adapt the Proactive Personality Scale–Short Version (PPS-SV) into the Indonesian language and test its validity and reliability in a student population. A total of 232 students (61 men, 171 women) from a university in Bandung participated in the study. The age range of the participants was 19–25 years old (M = 21.7; SD = 1.12). Construct validity was tested using confirmatory factor analysis (CFA), while reliability was estimated using Cronbach's alpha and McDonald's omega. The CFA results confirmed the one-factor structure of the PPS-SV and demonstrated good model fit with the data (CFI = .964, TLI = .954, GFI = .994, RMSEA = .069, and SRMR = .036). The scale also showed excellent internal consistency ($α$ = .901; $ω$ = 0.902). Thus, the Indonesian adaptation of the PPS-SV was judged to have strong psychometric properties, including good construct validity and reliability. This scale can therefore be recommended for measuring proactive personality in students in Indonesia.